Correction: Long non-coding RNA SNHG17 may function as a competitive endogenous RNA in diffuse large B-cell lymphoma progression by sponging miR-34a-5p. - Shengjuan Lu; Lin Zeng; Guojun Mo; Danqing Lei; Yuanhong Li; Guodi Ou; Hailian Wu; Jie Sun; Chao Rong; Sha He; Dani Zhong; Qing Ke; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0294729.].